Efektifitas dan Kontribusi Parawisata Terhadap Pendapatan Asli Daerah Kota Tidore Kepulauan - Majojo, Muhammad Yasin; Ruray, Titiek Arafiani; Toduho, Dessy Ayuni; Zulham, Muhammad (Peneliti.net, 2025)
This study aims to determine how (1) the contribution of the tourism sector to the local revenue of Tidore Island City. (2) To find out whether the income from the tourism sector has been effective and efficient. The data collection technique in this research uses several ways of interviewing, observing, documenting, and studying literacy about the problem under study. , the method of analysis in this study includes: data collection, data reduction, data presentation and drawing conclusions. Based on data analysis carried out in the period 2018 to 2021, it can be seen that the level of effectiveness of the parawista retribution with an average value of 1.57% with the criteria of the achievement level being ineffective, while the average is 0.63% with very efficient criteria.